Diabetes mellitus as a risk factor for periimplantitis - Guevara Callire , Liz Yannett (2021)
Diabetes mellitus is a chronic endocrine disease that is considered an important risk factor for the development of periodontal and peri-implant diseases due to its inflammatory nature. The objective of this review is to argue what scientific evidence exist on diabetes mellitus as a risk factor for the development of peri-implantitis. A bibliographic review of the last 10 years (January 2011 to January 2021) was carried out using search terms that included the keywords in English: (dental implants or oral implants) and (diabetes or diabetic), in search engines: PubMed and Embase (electronic databases). Concluding that although there is no conclusive evidence, it must be considered that there is a relationship between the presence of diabetes mellitus and peri-implantitis. For this reason, this disease should be considered as a risk factor for peri-implantitis, and it is advisable that diabetic patients should always keep their glucose level under control.